ANALYSIS OF STANDARD OPERATIONAL PROCEDURES (SOP) IN DOING SERVICES AND ITS INFLUENCE ON PATIENT SATISFACTION AT KLINIK MEDAN MEDICAL CENTER - Ikhwana, Hablil (RADJA PUBLIKA, 2021)
This study aims to find out what are the Standard Operating Procedures (SOPs) that must be applied in providing services to patients at the Klinik medan medical center. How does the application of Standard Operating Procedures (SOP) applied by employees in providing services to patients at the Klinik medan medical center on patient satisfaction. How much influence the application of Standard Operating Procedures (SOP) applied by employees in providing services to patients at the Klinik medan medical center on patient satisfaction. The method used in this study is a quantitative method with several tests, namely reliability analysis, and linear regression. Based on the results of the primary data regression which was processed using SPSS 20, the following simple linear regression equation was obtained: Y = 24.312 + 0, 405 X. Partially, the SOP variable (X) has a significant effect on patient satisfaction (Y) at the Klinik medan medical center. This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (4.025 > 1.986). The SOP variable (X) is able to contribute to the influence of the patient satisfaction variable (Y) by 39.4% while the remaining 60.6% is influenced by other variables not examined in this study. From the conclusions above, the authors suggest that employees and leaders should improve SOPs within the company's internal in order to provide excellent service to patients. Leaders and employees should maintain patient satisfaction by improving clinical facilities.